PERSEPSI KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN PUBLIK DI SISTEM ADMINISTRASI MANUNGGAL SATU ATAP KABUPATEN BOGOR - Asti Andayani; ichrisapuji@gmail.com (Economicus : Jurnal Ekonomi dan Manajemen, 2020)
This study aims to determine the level of performance of the Bogor Regency SAMSAT service on community satisfaction, then to know the level of expectation of the Bogor Regency SAMSAT service based on public opinion, and the last is to determine the level of disparity between performance and expectations of the Bogor Regency SAMSAT service. The population in this study were the taxpayers at SAMSAT Bogor Regency with a total sample of 100 respondents. Data collection techniques were carried out using surveys and questionnaires, while for data analysis using the help of Microsoft Excel 2007 software and SPSS version 22 to test, namely, validity tests, reliability tests, Service Quality (SQ), Customers Satisfaction Index (CSI), and Importance Performance Analysis. (IPA). The results showed that the index value of community satisfaction with the quality of service at SAMSAT Bogor Regency is currently 81.50%, which means that consumers are quite satisfied with the service system administration manunggal one atap Bogor Regency are not considered optimal overall, as for the most important expectations for the community is in the cleanliness and safety of the environment while the low level is in the discipline of officers so that the three factors must be improved and improved, all indicators of service quality get a negative gap.